Summation #1

Evaluate:

n = 0 ( n + 2 ) ! 2 n n ! \large \sum_{n=0}^{\infty} \frac{(n+2)!}{2^{n}n!}


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 25, 2018

S = n = 0 ( n + 2 ) ! 2 n n ! = n = 0 ( n + 1 ) ( n + 2 ) 2 n S = 2 2 0 + 6 2 1 + 12 2 2 + 20 2 3 + + ( n + 1 ) ( n + 2 ) 2 n + . . . ( 1 ) S 2 = 2 2 1 + 6 2 2 + 12 2 3 + 20 2 4 + + n ( n + 1 ) 2 n + . . . ( 1 ) 2 ( 2 ) S 2 = 2 2 0 + 4 2 1 + 6 2 2 + 8 2 3 + + 2 ( n + 1 ) 2 n + . . . ( 1 ) ( 2 ) ( 3 ) S 4 = 2 2 1 + 4 2 2 + 6 2 3 + 8 2 4 + + 2 n 2 n + . . . ( 3 ) 2 ( 4 ) S 4 = 2 2 0 + 2 2 1 + 2 2 2 + 2 2 3 + + 2 2 n + . . . ( 3 ) ( 4 ) ( 5 ) = 2 + 1 2 0 + 1 2 1 + 1 2 2 + Infinite geometric progression = 2 + 1 1 1 2 = 4 \begin{aligned} S & = \sum_{n=0}^\infty \frac {(n+2)!}{2^n n!} \\ & = \sum_{\color{#3D99F6}n=0}^\infty \frac {(n+1)(n+2)}{2^n} \\ S & = \frac 2{2^0} + \frac 6{2^1} + \frac {12}{2^2} + \frac {20}{2^3} + \cdots + \frac {(n+1)(n+2)}{2^n} + \cdots & \small \color{#3D99F6} ... (1) \\ \frac S2 & = \frac 2{2^1} + \frac 6{2^2} + \frac {12}{2^3} + \frac {20}{2^4} + \cdots + \frac {n(n+1)}{2^n} + \cdots & \small \color{#3D99F6} ... \frac {(1)}2 \to (2) \\ \frac S2 & = \frac 2{2^0} + \frac 4{2^1} + \frac 6{2^2} + \frac 8{2^3} + \cdots + \frac {2(n+1)}{2^n} + \cdots & \small \color{#3D99F6} ... (1)-(2) \to (3) \\ \frac S4 & = \frac 2{2^1} + \frac 4{2^2} + \frac 6{2^3} + \frac 8{2^4} + \cdots + \frac {2n}{2^n} + \cdots & \small \color{#3D99F6} ... \frac {(3)}2 \to (4) \\ \frac S4 & = \frac 2{2^0} + \frac 2{2^1} + \frac 2{2^2} + \frac 2{2^3} + \cdots + \frac 2{2^n} + \cdots & \small \color{#3D99F6} ... (3)-(4) \to (5) \\ & = 2 + \color{#3D99F6} \frac 1{2^0} + \frac 1{2^1} + \frac 1{2^2} + \cdots & \small \color{#3D99F6} \text{Infinite geometric progression} \\ & = 2 + {\color{#3D99F6}\frac 1{1-\frac 12}} = 4 \end{aligned}

Therefore S = 16 S = \boxed{16}

n = 0 ( n + 2 ) ! 2 n n ! = n = 0 1 2 n 1 ( n + 2 2 ) \sum_{n=0}^{\infty}\frac{(n+2)!}{2^nn!}=\sum_{n=0}^{\infty}\frac{1}{2^{n-1}}\binom{n+2}{2}

with some help form Pascal's formula, which says

( n + 1 k + 1 ) = ( n k + 1 ) + ( n k ) \binom{n+1}{k+1}=\binom{n}{k+1}+\binom{n}{k}

n = 0 1 2 n 1 ( n + 2 2 ) = n = 0 1 2 n 1 ( ( n + 1 2 ) + ( n + 1 1 ) ) \sum_{n=0}^{\infty}\frac{1}{2^{n-1}}\binom{n+2}{2}=\sum_{n=0}^{\infty}\frac{1}{2^{n-1}} \big( \binom{n+1}{2}+\binom{n+1}{1} \big)

n = 0 1 2 n 1 ( ( n + 1 2 ) + ( n + 1 1 ) ) = n = 0 1 2 n 1 ( ( n + 1 2 ) ) + n = 0 ( n + 1 2 n 1 ) \sum_{n=0}^{\infty}\frac{1}{2^{n-1}} \big( \binom{n+1}{2}+\binom{n+1}{1} \big)=\sum_{n=0}^{\infty}\frac{1}{2^{n-1}} \big( \binom{n+1}{2} \big) +\sum_{n=0}^{\infty} \big( \frac{n+1}{2^{n-1}}\big)

Generating functions can be utilised, if the above summations are written as below.

f ( x ) = n = 0 1 2 n 1 ( n + 2 2 ) x n = n = 0 1 2 n 1 ( n + 1 2 ) x n + n = 0 n + 1 2 n 1 x n f(x)=\sum_{n=0}^{\infty}\frac{1}{2^{n-1}}\binom{n+2}{2}x^n=\sum_{n=0}^{\infty}\frac{1}{2^{n-1}} \binom{n+1}{2} x^n +\sum_{n=0}^{\infty} \frac{n+1}{2^{n-1}} x^n

can be further simplified as

f ( x ) = 1 2 f ( x ) + 4 + x d d x ( 1 2 x ) + 3 2 x f(x)=\frac{1}{2}f(x)+4+x \frac{d}{dx}\big( \frac{1}{2-x} \big)+\frac{3}{2-x}

the rest is a simple derivative calculation and solving for f ( x ) f(x) . Finally evaluate f ( x ) f(x) for x = 1 x=1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...